The Relationship Between BIST100 Index Return and the Central Bank of the Republic of Turkey Interest Rate Decisions - Yılmaz, Yunus (My University, 2022)
Stock prices are affected by many economic and political factors. Interest rate, one of the macroeconomic indicators, is one of the important factors that are thought to affect share prices in the stock market. Central banks determine the interest rates of short-term loans given to banks and borrowing from banks. Through this interest rate, it aims to affect the general level of prices. A change in the interest rate changes the cost of borrowing and thus affects the firms’s profitability and ability to pay dividends. Again, change in interest rate can affect the opportunity cost of equity investments and this in turn affects stock prices. In this study, it is aimed to determine whether the interest rate decisions taken by the CBRT Monetary Policy Committee cause abnormal returns on stock prices. In Borsa Istanbul, the existence of abnormal returns with the effect of interest rate changes was investigated by event study method. Using 131-month data between May 2010 and March 2021, the presence of abnormal returns around the date of 30 meetings, when the decision to change the interest rate, was tested on the BIST100 index. As a result, it has been determined that interest rate change decisions have a very low effect on the BIST100 index. Although the effect on the index was observed within five days after the date of the interest rate increase/decrease decision, it was observed that this effect remained very weak.